School Leadership Enhances Secondary Students’ Achievement in Rural China Through Teacher Commitment and Collaborative Culture - Li, Ling; Zhu, Haixue; Li, Hui (Frontiers in Psychology, 2022)
The effect of school leadership (SL) on student achievement (SA) has been extensively examined, whereas the influences of teacher commitment (TC) and collaborative culture (CC) have not been thoroughly explored. This study conducted a moderated mediation analysis by investigating (a) TC as a mediator in the relationship between SL and SA and (b) CC as a moderator of the relationship between SL and SA. Altogether, 3134 (female =1673, 53.4%; male =1461, 46.4%) students and their 841 teachers from 80 middle schools in rural China were recruited and surveyed. SA was evaluated using PISA 2008 tests, including reading, math, and science, and SL, TC, and CC were evaluated using the Teaching and Leading in Schools Survey Scale. In addition, the “many to many” step was employed to match teachers’ data with the students’ data by STATA analysis. The results indicated that: (1) there were direct and indirect effects of SL on SA in the mediation model; (2) TC was confirmed as a full mediator between SL and SA; and (3) CC acted as a significant moderator of SL effects on SA through TC. Implications for improving school leadership and student achievement are discussed.